2019
DOI: 10.1103/physrevb.100.100503
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of superconductivity mediated by antiferromagnetic squeezed magnons

Abstract: We investigate theoretically magnon-mediated superconductivity in a heterostructure consisting of a normal metal and a two-sublattice antiferromagnetic insulator. The attractive electron-electron pairing interaction is caused by an interfacial exchange coupling with magnons residing in the antiferromagnet, resulting in p-wave, spin-triplet superconductivity in the normal metal. Our main finding is that one may significantly enhance the superconducting critical temperature by coupling the normal metal to only o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 79 publications
11
76
1
Order By: Relevance
“…We then still have the required signs in order to obtain a nontrivial solution to the gap equation, and obtain a boosting from the A-factor, for Ω < 1, in exactly the same way as was obtained in NM/AFMI case of Ref. [16]. For Ω = 0, the interaction potential is therefore much stronger than the potential we had in the FMI case.…”
Section: Pairingmentioning
confidence: 71%
See 2 more Smart Citations
“…We then still have the required signs in order to obtain a nontrivial solution to the gap equation, and obtain a boosting from the A-factor, for Ω < 1, in exactly the same way as was obtained in NM/AFMI case of Ref. [16]. For Ω = 0, the interaction potential is therefore much stronger than the potential we had in the FMI case.…”
Section: Pairingmentioning
confidence: 71%
“…The main result of the paper, which is expected to be ro-bust, is that the strength of the fermion-fermion interaction mediated by antiferromagnetic magnons, analogously to the NM/AFMI case of Ref. [16], is enhanced by coupling asymmetrically to the two sublattices of the AFMI. The interaction strength is therefore significantly larger than for an FMI.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].Research interest in antiferromagnetic materials is surging [11,12]. This enthusiasm is due to the promising properties of antiferromagnets such as high resonance frequencies in the THz regime and a vanishing net magnetic moment.…”
mentioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%